Feasibility study on addition of a colourant to commercially used fire-retardant formulations to enable visual distinguishability between treated and untreated mine support timber - Du Toit, C. B. (Stellenbosch : Stellenbosch University, 2012)
Thesis (M. Sc.) -- University of Stellenbosch, 1991.